An enhancement of binary particle swarm optimization for gene selection in classifying cancer classes - Mohd Saberi, Mohamad; Sigeru, Omatu; Safaai, Deris; Yoshioka, Michifumi; Afnizanfaizal, Abdullah; Zuwairie, Ibrahim (BioMed Central Ltd., 2013)
Gene expression data could likely be a momentous help in the progress of proficient cancer diagnoses and classification platforms. Lately, many researchers analyze gene expression data using diverse computational intelligence methods, for selecting a small subset of informative genes from the data for cancer classification. Many computational methods face difficulties in selecting small subsets due to the small number of samples compared to the huge number of genes (high-dimension), irrelevant genes, and noisy genes.